Smart Pool System - Abuzaneh, Shaymaa; Hasasneh, Linda; Aldawdeh, Marwa (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2021)
Due to the increase in drowning cases, the lack of pure water, and increasing or decreasing the temperature of water in the pool. So, monitoring of swimming pool has become one of the daily routine tasks that may consume time and effort and may be dangerous at times in deep pools. The need for an automated system arose to monitor the swimming pool and the ability to know data remotely through the webpage. Our project seeks to provide a system that performs several operations, including checking the quality of water. Also, this system checks the temperature of the water in the pool to avoid some problems that may occur, especially when the water freezes. Also, the system measures the temperature of pool water then the system will turn on the heater. This system also deals with drowning cases that may occur. Therefore, this system provides the inhabitant with all the information that it may need from anywhere he is located through a webpage without time or effort and without the need to manually check the pool. The system has been built and verified to meet the requirements of this project, and it was found that it performs as it should and meets the needs of the project.
no of pages 47, هندسة حاسوب 21/2021